Co-infection of Salmonella enteritidis with H9N2 avian influenza virus in chickens. Issue 5 (2nd September 2020) - Arafat, Nagah; Abd El Rahman, Sahar; Naguib, Doaa; El-Shafei, Reham A.; Abdo, Walied; Eladl, Abdelfattah H.
ABSTRACT: Salmonella and avian influenza virus are important pathogens affecting the poultry industry and human health worldwide. In this experimental study, we evaluated the consequences of co-infection of Salmonella enteritidis (SE) with H9N2 avian influenza virus (H9N2-AIV) in chickens. Four groups were included: control group, H9N2-AIV group, H9N2-AIV + SE group, and SE group. Infected chickens were intranasally inoculated with H9N2-AIV at 21 days of age and then orally administered SE on the same day. The birds were monitored for clinical signs, mortality rates, and alterations in body weight. Sera, intestinal fluids, oropharyngeal, and cloacal swabs, and tissue samples were collected at 2, 6, 10, and 14 days post-infection (dpi). Significant increases in clinical signs and mortality rates were observed in the H9N2-AIV + SE group. Moreover, chickens with co-infection showed a significant change in body weight. SE faecal shedding and organ colonization were significantly higher in the H9N2-AIV + SE group than in the SE group. H9N2-AIV infection compromised the systemic and mucosal immunity against SE, as evidenced by a significant decrease in lymphoid organ indices as well as systemic antibody and intestinal immunoglobulin A (IgA) responses to SE and a significant increase in splenic and bursal lesion scores. Moreover, SE infection significantly increased shedding titres and duration of H9N2-AIV. In conclusion, this is the first report of co-infection of SE with H9N2-AIV in chickens, which leads to increased pathogenicity, SE faecal shedding and organ colonization, and H9N2-AIV shedding titre and duration, resulting in substantial economic losses and environmental contamination, ultimately leading to increased zoonoses.